Economic security of regions: A methodological approach to assessment, management, and legal regulation - Ohla Ovcharenko; Larysa Korotka; Viktoriia Smiesova; Ohla Kuchkova; Roman Karpenko (REGION, 2022)
At the present stage of development, one of the major problems of regions is ensuring their economic security. This requires the development of effective methodological approaches to assess economic security at the regional level by governing bodies, and the development of directions for regulating economic security at the local and state levels. The purpose of the article is to form methodological tools for assessing the economic security of regions based on the method of fuzzy modeling, to develop approaches to managing the economic security of a region by public authorities and local governments. The article has proposed and analyzed indicators for assessing the economic security of regions. The scientific novelty of the article is the use of fuzzy modeling to assess the economic security of regions. This method, unlike others, allows you to use fuzzy input data in simulation modeling and obtain output data that can be reduced to crisp values using defuzzification methods. The expediency of using fuzzy logic tools to assess economic security at the meso-level has been substantiated. The effectiveness of the practical application of the proposed approach has been tested based on assessing the economic security of the regions in Ukraine. The integral index of economic security has been modelled, together with its components: investment, innovation, financial, foreign economic, demographic, social security, and security of economic activity. For the demonstration of the practical application of the proposed methodological approach, the data of 10 regions of Ukraine has been analyzed and their economic security has been assessed. The directions of economic and legal regulation of the analyzed regions of Ukraine, which are characterized by crisis and low level of economic security and its components, have been offered.
Keywords: 330; economic security; fuzzy logic; legal regulation; management; method of fuzzy modeling; region